Optimizing Young Jackfruit (Artocarpus heterophyllus Lam.) Processing for Plant-Based Meatballs: Impact of Thermal Treatments on Quality Parameters and Organoleptic Properties - Wisutthana Samutsri; Sujittra Thimthuad (International Journal of Food Science)
As global demand for plant-based foods increases due to their nutritional and environmental benefits, young jackfruit (Artocarpus heterophyllus) is emerging as a promising meat alternative. This study evaluates the effects of heat treatments—specifically blanching for 5 min and boiling for 15, 30, and 45 min—on the quality and sensory attributes of jackfruit-based meatballs. The results indicate consistent color values (L∗, a∗, and b∗) across the samples, with L∗ values ranging from 53.68 to 54.92 and a∗ values from 3.02 to 3.38. The browning index increased with longer boiling times, while the water holding capacity improved from 2.22 to 4.35 as the cooking time extended. Blanching increased the hardness (536.93 g) and springiness (8.30%) of the meatballs. However, these properties decreased with longer boiling times, reaching 317.44 g and 7.68%, respectively, after 45 min. Sensory analysis revealed a strong preference for meatballs made from young jackfruit boiled for 45 min, with the highest score in appearance, flavor, and overall acceptability. These findings suggest that boiling young jackfruit for 45 min optimizes its texture and sensory qualities, highlighting its potential as a sustainable, nutritious, and appealing ingredient for plant-based meat substitutes.